OPTIMALISASI KINERJA KARYAWAN DI KONVEKSI ARENSA JAYA VARIASI MENGGUNKAN ANALISIS PENUGASAN - Rini Merdiani; Dania Nuraeni; Sri Laila Nurfatihani; Somadi Somadi (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
Arensa Jaya Variasi Convection, a small and medium-sized garment manufacturing enterprise SME, faces challenges in its employee Assignmentsystem because the allocation of workers to four workstations pattern making, cutting, sewing, and packing is still carried out using conventional practices and is not based on each employee's skills and task completion time. This condition Results in an uneven distribution of workload, increased production time, and inefficient operational costs. This study aims to optimize employee assignments at Arensa Jaya Variasi Convection. The research employed a descriptive quantitative approach using the Hungarian Method. The Results indicate that the optimal Assignmentis Sopiyan to the pattern-making workstation 20 minutes, Fajrin to the cutting workstation 25 minutes, Deni to the sewing workstation 90 minutes, and Dian to the packing workstation 15 minutes, Resulting in a total completion time of 150 minutes. These findings demonstrate that the Hungarian Method is effective in optimizing employee assignments in the garment manufacturing operations of Arensa Jaya Variasi.